The impact of perceived career opportunity to employees turnover intention mediated by organizational commitment - Leonardi, Vincent; Panggabean, Hana Rochani Gustasari (Jurnal Psikologi Ulayat, 2021)
Work termination that is initiated by employees is crucial to be identified because it potentially reduces company productivity. Positive career opportunities perceived by employees could reduce their intention to quit because employees can evaluate the match between their work and their interests and, therefore, they perceive that the company provides an opportunity for their career pathway. This study was conducted on a retail company that was facing high work employees-initiated termination (24.75% annually) and aims to examine the influence of employees’ perceptions of career opportunities on their intention to quit mediated by employees’ levels of organizational commitment. A total of 148 employees participated in the survey where their data were analyzed using simple mediation analysis. The results showed that affective and continuance commitment partially mediated the influence between employees’ perception of career opportunities on their intention to quit. The study potentially informs organizations facing high rates of employee-initiated termination by providing career opportunity that allows employees to increase their organizational commitment.